Muscle Activity and Kinematics During Three Hamstring Strengthening Exercises Compared to Sprinting: A Cross-Sectional Study. - Adelso Jorge; Eric Lichtenstein; Oliver Faude; Ralf Roth (International Journal of Sports Physical Therapy, 2024)
# Background